Optimizing Bacterial Protectant Composition to Enhance Baijiu Yeast Survival and Productivity During Spray Drying - Jingyu Li; Fengkui Xiong; Zhongbin Liu; Jia Zheng; Guangzhong Hu; Zheng Feng (Fermentation)
The flavor substances produced by the division of baijiu yeast during the winemaking process often determine the quality of white wine, and the difficulty of storing and transporting high-quality baijiu yeast is a bottleneck that restricts the development of China’s baijiu industry. It is widely accepted that drying microorganisms such as baijiu yeast is the best way to improve its storage and transport performance. Spray drying, as one of the most widely used microbial drying processes, with a high efficiency and low cost, is the hot spot of current research in the field of microbial drying, but it has the inherent defect of a low drying survival rate. In order to address this inherent defect, the present study was carried out with a high-quality white wine yeast, Modified Sporidiobolus Johnsonii A (MSJA), as the target. Firstly, an orthogonal experiment, Steep Hill Climbing experiment, and response surface experiment were sequentially designed to optimize the type and amount of protective agent added in the spray-drying process of MSJA. Then, the effects of glutamyl transaminase (TGase) treatment on the drying process of MSJA were revealed with the help of advanced equipment, such as laser particle sizer, environmental scanning electron microscope (ESEM), and Fourier-transform infrared scanner (FTIR). The results showed that the addition of “TGase-treated soybean isolate protein (SPI) + lactic protein (LP)” as an in vitro bacterial protectant and “14.15% trehalose + 7.10% maltose + 14.04% sucrose” TGase treatment can promote the cross-linking of protective proteins, reduce the distance between MSJA bacteria and protective proteins, and increase the glass transition temperature to enhance the protective effect of protective proteins, so as to improve the survival rate of MSJA during spray drying.